2006
DOI: 10.1038/sj.bjc.6603261
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic impact of the protein tyrosine phosphatases PRL-1, PRL-2, and PRL-3 in breast cancer

Abstract: The aim of this study was to investigate the expression of the protein tyrosine phosphatases (PTP) PRL-1, PRL-2, and PRL-3 in human breast cancer and to evaluate its clinical and prognostic significance. PRL-PTP mRNA expression was examined in malignant (n ¼ 7) and nonmalignant (n ¼ 7) cryoconserved breast tissue samples as well as in eight breast cancer cell lines by RT -PCR. Furthermore, protein expression of PRL-3 was analysed semiquantitatively by immunohistochemistry in ductal breast carcinoma in situ (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
106
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 40 publications
6
106
1
Order By: Relevance
“…[16][17][18] More importantly, PTP4A3 is upregulated in clinically malignant cancer specimens compared with their benign counterparts in multiple human cancers and is associated with poor prognosis. 12,16,19,20 Recently, endosomes were shown to play an important function in autophagy, fusing with autophagosomes prior to lysosomal fusion for cargo degradation. [21][22][23] Since PTP4A3 and its close homolog PTP4A1 both have endosomal localization, 10,24 we investigated whether they were functionally linked to autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] More importantly, PTP4A3 is upregulated in clinically malignant cancer specimens compared with their benign counterparts in multiple human cancers and is associated with poor prognosis. 12,16,19,20 Recently, endosomes were shown to play an important function in autophagy, fusing with autophagosomes prior to lysosomal fusion for cargo degradation. [21][22][23] Since PTP4A3 and its close homolog PTP4A1 both have endosomal localization, 10,24 we investigated whether they were functionally linked to autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatase of regenerating liver-3 (PRL-3) was identified as the only gene that is consistently overexpressed in liver metastases derived from colorectal cancer (CRC), whereas it is undetectable in normal colorectal epithelia and shows intermediate expression in advanced primary cancer. 1 Increasing evidence suggests that PRL-3 plays multiple roles in cancer migration and metastasis: PRL-3 expression is elevated in most metastatic lesions from various human malignancies including those of the colorectum, 2,3 stomach, 4 mammary gland 5 and ovary. 6 In the in vivo cancer-metastasis models, overexpression of PRL-3 in Chinese hamster ovary (CHO) cells promoted the incidence of metastasis, 7,8 and knockdown of PRL-3 expression in CRC-derived DLD-1 cells by RNA interference effectively abrogated the activities of cancer cell motility in vitro and hepatic colonization in vivo.…”
mentioning
confidence: 99%
“…6 In the in vivo cancer-metastasis models, overexpression of PRL-3 in Chinese hamster ovary (CHO) cells promoted the incidence of metastasis, 7,8 and knockdown of PRL-3 expression in CRC-derived DLD-1 cells by RNA interference effectively abrogated the activities of cancer cell motility in vitro and hepatic colonization in vivo. 3 The PRL family members (PRL-1, PRL-2 and PRL-3) comprise a distinct subclass of protein tyrosine phosphatases (PTPs), 9 whereas the C(X) 5 R motif within the P-loop of the PRL-3 protein is typical for dual-specific phosphatases: It is close in structure to the Rho-type small GTP-binding protein (GTPase) Cdc42, and to phosphatase tensin homologues deleted on chromosome 10 (PTEN). 10 The catalytic domain of the PRL-3 protein is critical for its regulation of PRL-3-mediated cancer cell migration and invasion: site-directed mutagenesis experiments revealed that catalytic domain-mutants of PRL-3 (C104A) within the P-loop diminished PRL-3-induced invasion and Rho activation in CRCderived SW480 cells.…”
mentioning
confidence: 99%
“…Overexpression of PRL-1 and PRL-2 transformed mouse fibroblasts and hamster pancreatic epithelial cells in culture (Cates et al, 1996), and promoted tumour growth in nude mice (Diamond et al, 1994). PRL-3 gene, located in 8q24-3, has been involved in processes of migration, invasion and metastasis in different types of cancer (Miskad et al, , 2007Wu et al, 2004;Polato et al, 2005;Radke et al, 2006;Wang et al, 2006;Qian et al, 2007). Initially, specific overexpression of PRL-3 in colorectal cancer liver metastases (LMs) was observed when compared with matched primary tumours in association with gene amplification (Saha et al, 2001;Bardelli et al, 2003).…”
mentioning
confidence: 99%